Android Programming : the Big Nerd Ranch guide - Marsicano, Kristin, ....-; Gardner, Brian, ....-; Phillips, Bill, ....- (Atlanta (Ga.) : Big Nerd Ranch, 2019)
Dive in to learn the foundations of Android application development. The content is now in Kotlin and updated with modern Android practices. What you'll learn: How screens are represented with Activities, Fragments, and Views. Dealing with Android's main thread and how to do work in the background. Different ways to store data locally on the device. How to make web requests to fetch data from a remote server.
Keywords: Android; Programming